Functional outcome of distal femoral fractures treated with distal femoral locking compression plate: a cross-sectional study - Kumar Deep, Sandeep Kumar; Phogat, Varun; Debroy, Sankar (International Journal of Research in Orthopaedics, 2025)
Background: Despite advances in fixation techniques, distal femoral fractures still pose significant challenges for orthopedic surgeons. Effective treatment hinges on a detailed understanding of local anatomy, accurate clinical and imaging assessments, recognition of the fracture morphology, and the judicious choice of a fixation device suited to the particular case. Locking compression plates (LCPs), with their numerous advantages such as enhanced stability, fixed-angle screw locking, and minimal disruption to periosteal blood supply have proven to be highly effective in addressing these challenges and are especially valuable in osteoporotic bone. Methods: This cross-sectional study was conducted at a tertiary care institution in Tripura between October 2016 and September 2019, comprising 60 patients with distal femoral fractures who underwent open reduction and internal fixation utilizing a distal femoral locking compression plate (DF-LCP). The functional outcome was assessed using Neer’s criteria. Results: The study included 60 patients, of whom 42 were male and 18 were female. The majority of fractures (70%) were attributed to road traffic accidents. The mean duration for radiological evidence of fracture union was 17.2 weeks. According to Neer’s criteria, the final functional outcome of the knee was rated as excellent in 34 patients (56.7%), good in 20 patients (33.3%), fair in 5 patients (8.33%), and poor in 1 patient (1.67%). Conclusions: Surgical fixation of distal femoral fractures with distal femoral LCP provides good functional outcome and is one of the best modalities of treatment available for these kinds of fractures especially in severely comminated and in osteoporotic cases.